2002
DOI: 10.1034/j.1399-6576.2002.460516.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate attenuates intracellular acidosis

Abstract: During exercise-induced metabolic acidosis, intravenous administration of bicarbonate increased the buffering capacity of blood and attenuated the decrease in intracellular muscle pH, although there was a small increase in the arterial carbon dioxide pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 18 publications
4
43
0
Order By: Relevance
“…A similarly low pH i value of 6.2 (Achten et al 1990), 6.3 (Boushel et al 1998a), or even 5.6 (Nielsen et al 2002), has been measured with 31 P-MRS during forearm exercise. It should be considered that the intramuscular proton concentration reaches an upper limit perhaps set by inhibition of the key regulatory glycolytic enzyme 6-phosphofructo-1-kinase (Costa Leite et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similarly low pH i value of 6.2 (Achten et al 1990), 6.3 (Boushel et al 1998a), or even 5.6 (Nielsen et al 2002), has been measured with 31 P-MRS during forearm exercise. It should be considered that the intramuscular proton concentration reaches an upper limit perhaps set by inhibition of the key regulatory glycolytic enzyme 6-phosphofructo-1-kinase (Costa Leite et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Even though pH i was 15% lower in the arms compared with the tibialis anterior muscle, we recognize that this is also compounded by the (Hermansen and Osnes 1972;Sahlin et al 1978;Boushel et al 1998a, b;Nielsen 1999) are presented for comparison. The full square shows the intracellular proton concentration corresponding to the venous proton concentration from Nielsen et al 2002 according to the predictive equation y = 4.3x (r 2 = 0.65) of the linear regression fitting of the present data specificity of the motor recruitment protocol and the test subjects. Third, it was assumed that other tissues did not take up the lactate released to the extracellular space in significant amounts during the exercise bout and the relevant recovery provided.…”
Section: Limitations Of the Anaerobic Capacity Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Stackhouse et al (2001) suggested that the muscular contraction process seems to be limited by acidosis which can be considered as the main cause of muscular fatigue during supra-maximal exercise. Taking into account the close relationship which binds the H + ions to , the concentration decrease in blood [HCO 3 -] seems to account for the acidosis level induced by exercise (Nielsen et al 2002). Then, the longer t lim observed during IE P could be explained by the higher pH and values observed at the end of this exercise (Fig.…”
Section: Effects Of Recovery Mode On Total Exercise Duration (T Lim )mentioning
confidence: 96%
“…NaHCO 3 contained in BRS is the most biologically suitable alkalinizing reagent for its prompt alkalization effect [14], because HCO 3 Ϫ can be directly produced from NaHCO 3 without a metabolic process. Several investigators reported concerning the efficacy of NaHCO 3 on acidosis [15][16][17][18]. In the present study, we evaluated the effects of several RS, BRS, ARS, LRS, and RS, on metabolic acidosis, serum electrolyte abnormality and circulatory failure in haemorrhagic shock model with dogs, an experimental animal model mimicking massive bleeding.…”
Section: Discussionmentioning
confidence: 99%